Hafız Esad’ın Kararları: Olasılık Teorisi Bağlamında Bir İnceleme - Dilek CANYURT (Gazi Akademik Bakış)
Hafez Assad, who ruled Syria for nearly 30 years, draws attention as an important leader in the political history of the country. Assad was not only a leader, but also the sole power in the country. The regime he built was shaped under the umbrella of the Baath party, and this party became the institutionalized version of Assad, as it were. After his death, the Baath regime continues with his son Bashar Assad in Syria, despite the Civil War environment. Hafez Assad’s ability to be this strong is owing to the decisions he made both in his personal life and in his political life Assad’s strategic decisions determined the future of Syria as well. Analyzes of leaders have drawn attention as one of the most important fields in political studies. Leadership studies are generally included in decision making theories. In this study, Assad’s decisions were analyzed from the perspective of prospect theory through analytical examples, Prospect theory is included in decision-making theories. As a result, it was determined that the important decisions Assad made in his life supported the assumptions of prospect theory.